Dissection of major QTLs and candidate genes for seedling stage salt/drought tolerance in tomato - Xin Li; Xiyan Liu; Feng Pan; Junling Hu; Yunhao Han; Ripu Bi; Chen Zhang; Yan Liu; Yong Wang; Zengwen Liang; Can Zhu; Yanmei Guo; et al. (BMC Genomics)
Abstract Background As two of the most impactful abiotic stresses, salt and drought strongly affect tomato growth and development, especially at the seedling stage. However, dissection of the genetic basis underlying salt/drought tolerance at seedling stage in tomato remains limited in scope. Results Here, we reported an analysis of major quantitative trait locus (QTL) and potential causal genetic variations in seedling stage salt/drought tolerance in recombinant inbred lines (n = 201) of S. pimpinellifolium and S. lycopersicum parents by whole genome resequencing. A total of 5 QTLs on chromosome 1, 3, 5, 7 and 12 for salt tolerance (ST) and 15 QTLs on chromosome 1, 3, 4, 8, 9, 10, 12 for drought tolerance (DT) were identified by linkage mapping. The proportion of phenotypic variation explained (PVE%) by these QTLs ranged from 4.91 to 15.86. Two major QTLs qST7 and qDT1-3 were detected in both two years, for which two candidate genes (methionine sulfoxide reductase SlMSRB1 and brassinosteroid insensitive 1-like receptor SlBRL1) and the potential functional variations were further analyzed. Taking advantage of the tomato population resequencing data, the frequency changes of the potential favorable QTL allele for seedling stage ST/DT during tomato breeding were explored. Conclusions These results will be beneficial for the exploration of salt/drought tolerance genes at seedling stages, laying a foundation for marker-assisted breeding for seedling stage salt/drought tolerance.